Evolution of plant cell wall: Arabinogalactan-proteins from three moss genera show structural differences compared to seed plants. (1st May 2017) - Bartels, Desirée; Baumann, Alexander; Maeder, Malte; Geske, Thomas; Heise, Esther Marie; von Schwartzenberg, Klaus; Classen, Birgit
Highlights: The study presented confirms that AGPs are present at the evolutionary stage of bryophytes. The three moss AGPs show unique structural features not known from higher plants. Moss AGPs are characterized by T-Rha and the unusual monosaccharide 3- O -Me-Rha not occurring in seed plants. One feature of the galactan core is the unusual branching point 1, 2, 3-Gal, which has not been detected in any AGP before. The presented data contributes to further understanding of plant cell wall evolution. Abstract: Arabinogalactan-proteins (AGPs) are important proteoglycans of plant cell walls. They seem to be present in most, if not all seed plants, but their occurrence and structure in bryophytes is widely unknown and actually the focus of AGP research. With regard to evolution of plant cell wall, we isolated AGPs from the three mosses Sphagnum sp., Physcomitrella patens and Polytrichastrum formosum . The moss AGPs show structural characteristics common for AGPs of seed plants, but also unique features, especially 3- O -methyl-rhamnose (trivial name acofriose) as terminal monosaccharide not found in arabinogalactan-proteins of angiosperms and 1, 2, 3-linked galactose as branching point never found in arabinogalactan-proteins before.